Percutaneous Rotational Mechanical Atherectomy Plus Thrombectomy Using Rotarex S Device in Patients With Acute and Subacute Lower Limb Ischemia: A Review of Safety, Efficacy, and Outcomes - Loffroy, Romaric; Falvo, Nicolas; Galland, Christophe; Fréchier, Léo; Ledan, Frédérik; Midulla, Marco; Chevallier, Olivier (Frontiers in Cardiovascular Medicine, 2020)
Acute and subacute ischemia of lower limbs is associated with high risk of amputation and potential severe life-threatening complications. Despite a lack of clear therapeutic recommendations, surgical treatments such as thrombectomy or bypass and/or catheter-directed thrombolysis (CDT) have been first-line procedures in both acute and subacute limb ischemia, but each therapy may lead to significant morbidity and mortality. Such situations demand fast restoration of appropriate flow to preclude limb loss and other complications. Percutaneous mechanical atherectomy plus thrombectomy (MATH) represents a minimally invasive approach for quickly recanalizing thrombus-containing lesions whatever the age of thrombus. Indeed, many chronic patients can present with critical limb ischemia, with thrombus-containing occlusive lesions triggered by underlying atherosclerotic disease. MATH offers various advantages over surgery and CDT, with lower invasiveness, faster recanalization, and the possibility to immediately treat the underlying lesions, with a lower rate of bleeding complications and no need for intensive care unit stay. Currently, several mechanical thrombectomy devices are offered as an alternative therapy and can be divided into pure rotational MATH systems and rheolytic thrombectomy devices. The only pure rotational MATH device currently available on the market is the Rotarex S device. We aimed to review contemporary clinical data regarding the safety, efficacy, and outcomes of MATH therapy using Rotarex S catheter in acute and subacute thrombus-containing arterial lesions of lower limbs. Future perspectives of Rotarex S MATH treatment and cost-effectiveness of its routine use will be also discussed.